Analisa Pengaruh Influencer Social Media Terhadap Keputusan Pembelian Konsumen Generasi Z di Kota Surabaya - Amalia, Adhimurti Citra; Sagita, Gabriella (Universitas Merdeka Madiun, 2019)
Social media influencers have now been used by many commercial brands as one of the promotional strategies to market their products. Especially for Z generation who are close to the use of the internet, social media, and digital media in their daily lives. Although the existence of social media influencers is on the rise, the trust of commercial brands to advertise their products on conventional media such as televisions is still quite high compare to the digital media. This issue encourages researchers to dig deeper whether social media influencers really influence the purchasing decisions of Z generation consumers in Surabaya city or not. In addition to measure the influence, researchers also want to know what factors are related to social media influencers that influence the purchasing decisions of Z generation consumers. This research uses quantitative methods where data collection is obtained through questionnaires. The results of the research were analyzed using Pearson Product Moments and it was found that Chi-square value (239.088) > Chi-Square table (42.557) and P-value (0.000) < alpha (0.05) which leads to the decline of H0, which indicates that there is an influence between social media influencers variables (independent / X) with generation Z consumer purchasing decision variables (dependent / Y).Keywords: influencer, social media, marketing strategy, consumer behaviour.